Illegal Trade of Marine Mammal Bone Exposed: Simple Test Identifies Bones of “Mermaid Ivory” or Steller's Sea Cow (Hydrodamalis gigas) - Crerar, Lorelei D.; Freeman, Elizabeth W.; Domning, Daryl P.; Parsons, E. Christien Michael (Frontiers in Marine Science, 2017)
In the US, marine mammals in the US are protected by the Endangered Species Act (ESA) and the Marine Mammal Protection Act (MMPA). Most of these species are listed by CITES and thus international trade in their products is restricted. Therefore, commercial sale of unfossilized marine mammal bone is largely prohibited. Sale of Steller’s sea cow (Hydrodamalis gigas) bone is legal, however, since the animals have been extinct since 1768. The current study outlines a simple test that can identify bone which is bona fide Steller’s sea cow – and thus legal to sell. The test uses a segment of the D-loop of the mitochondrion, which has the power to exclude samples which are not specifically H. gigas or a Sirenian relative. The test also includes a reliable method to extract DNA from bone and amplify it using PCR. Extracted DNA was sequenced to verify that only manatees, dugongs, elephants and their relatives produced a positive result. Using this test, products being sold commercially as legal “mermaid ivory” (Steller sea cow bone) were found to actually come from gray whale (Eschrichtius robustus), pantropical spotted dolphin (Stenella attenuata) and white-beaked dolphin (Lagenorhynchus albirostris) bone. This finding indicates that government agencies should monitor bones being sold as “mermaid ivory” because protected species are being illegally traded under the guise of being legal Steller’s sea cow bone.